1974
DOI: 10.1111/j.1476-5381.1974.tb09708.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorpropamide on Water Balance in Pitressin‐treated Brattleboro Rats

Abstract: 1 The daily administration of a 5% glucose solution to the heterozygous Brattleboro rat produced an experimental model in a comparable state of polydipsia and polyuria to the homozygous rat with diabetes insipidus (DI). 2 The effect of chlorpropamide on water metabolism was then examined in both the homozygous DI rat treated with submaximal doses of pitressin tannate in oil (Pitressin), and in the glucose-hydrated heterozygous rat with and without simultaneous pitressin therapy. 3 A dose-response curve for chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Experiments on AQP2 localization and urine concentration were performed to confirm that the BB rats used in our experiments indeed responded appropriately to DDAVP treatment (27,55). As expected, DDAVP induced a sustained, time-dependent increase in urine osmolality in BB rats (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Experiments on AQP2 localization and urine concentration were performed to confirm that the BB rats used in our experiments indeed responded appropriately to DDAVP treatment (27,55). As expected, DDAVP induced a sustained, time-dependent increase in urine osmolality in BB rats (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies showed that a reduction of urinary output is also correlated with reduced water intake in VPtreated Brattleboro rats. 48,49 Furthermore, although acute treatment of Brattleboro rats with physiologic doses of VP had no reported effect on GFR, 50,51 direct measurements of GFR were not performed in these studies, and a contribution of a change in GFR to the observed effect of CT cannot be ruled out.…”
Section: Discussionmentioning
confidence: 90%
“…Brattleboro rats lacking AVP because of spontaneous mutation of the AVP gene , were treated with intraperitoneal administration of simvastatin to a final plasma concentration of 200 μM, without any visible side effect . Simvastatin caused a decrease in urinary volume associated with consistently increased urine osmolality.…”
Section: Vasopressin‐independent Signals Regulating Aqp2 Trafficking mentioning
confidence: 99%